The essence and content of scientific research methodology - O. Mozolev; O. Polishchuk (Kazimierz Wielki University, 2024)
The article analyzes the essence and content of the concepts "methodology", "methods of scientific research". The content of general and special methods of conducting scientific research is disclosed. It has been established that the methodology of scientific research is a conceptual statement of the content, purpose, and methods of research that allow obtaining the most objective, systematized and accurate information about phenomena and processes. The methodology systematizes the methods, methods and methods of learning objective reality, ensuring the reliability of the obtained knowledge about the object of research, their compliance with the subject of research, and is also a means of substantiating the results and conclusions of the conducted scientific research. The methods of scientific research mean a set of cognitive rules and techniques, implemented in the form of interconnected operations, designed to obtain new knowledge, consisting of three stages: research, proof and explanation. Methods are a set of techniques and methods of activity that allow a person or organization to achieve set goals. The choice of methods depends on the nature and content of the problem, the terms and resources allocated for its study, the amount and quality of available information. The authors characterized the content of empirical, theoretical and special methods of scientific research. It has been established that general scientific methods provide an opportunity in the process of scientific research to determine only general approaches to the defined scientific problem. Special methods allow obtaining specific knowledge, answers to questions from the subject area of research.